A Need Analysis of English For Specific Purposes (ESP) For Nursing Students At SMKS Kesehatan Kendari - Ria Z Wulandari; Muhammad Khusnun Muchsin; Tambunan Tambunan (Universitas Bengkulu, 2019)
English for Specific Purposes (ESP) has been discussed for a long time around the world in the field of English Language Teaching (ELT). Teaching English based on students’ needs is important, particularly for those learners who learn English beyond the academic purposes such as vocational high school students. The objective of this study is to analyse nursing students’ needs for ESP materials at SMKS Kesehatan Kendari based on Target Situation Analysis. Therefore, this study is conducted to identify the Target Situation Analysis (TSA) of one of vocational high school in Kendari. This study employed research and development design with 22 samples. The data obtained from questionnaire were analysed statistically by using SPSS version 16.0. The result shows that students need in learning English process for the tasks of speaking skill; how to ask question English well, how to answer question English well, do communication with schoolmates, do communication with teachers, and do communication with patients. Listening skill; listening and understanding when do face to face conversations, listening and understanding through conversation on the phone, listening and understanding the content of forum discussions, and listening and understanding the content of announcements. Reading skill; how to read health magazine, how to read announcement, and how to read patient list, and Writing skill; how to fill the patients form and how to write medical report. Based on the findings, it concludes that speaking and listening skills are the most needed by nursing students in order to communicate in English.Keywords: English for Specific Purposes (ESP), Need Analysis, Target Situation Analysis (TSA), Nursing Students